Barrier Modification by Methyl Violet Organic Dye Molecules of Ag/P-Inp Structures (European Journal of Formal Sciences and Engineering, 2023)
This work includes fabrication and electrical characterization of Metal/Interlayer/Semiconductor (MIS) structures with methyl violet organic film on p-InP wafer. Metal(Ag)/ Interlayer (methyl violet =MV)/Semiconductor(p-InP) MIS structure presents a rectifying contact behavior. The values of ideality factor (n) and barrier height (BH) for the Ag/MV/p-InP MIS diode by using the current-voltage (I-V) measurement have been extracted as 1.21 and 0.84 eV, respectively. It was seen that the BH value of 0.84 eV calculated for the Ag/MV/p-InP MIS structure was significantly higher than the value of 0.64 eV of Ag/p-InP control contact. This situation was ascribed to the fact that the MV organic interlayer increased the effective barrier height by influencing the space charge region of inorganic semiconductor. The values of diffusion potential and barrier height for the Ag/MV/p-InP MIS diode by using the capacitance-voltage (C-V) measurement have been extracted as 1.21 V and 0.84 eV, respectively. The interface-state density of the Ag/MV/p-InP structure was seen to change from 2.57×1013 eV-1cm-2 to 2.19×1012 eV-1cm-2.
Keywords: Organic dye film; MIS diode; Series resistance; Interface states